2017
DOI: 10.1128/jvi.00034-17
|View full text |Cite
|
Sign up to set email alerts
|

Imaging HIV-1 Genomic DNA from Entry through Productive Infection

Abstract: In order to track the fate of HIV-1 particles from early entry events through productive infection, we developed a method to visualize HIV-1 DNA reverse transcription complexes by the incorporation and fluorescent labeling of the thymidine analog 5-ethynyl-2=-deoxyuridine (EdU) into nascent viral DNA during cellular entry. Monocyte-derived macrophages were chosen as natural targets of HIV-1, as they do not divide and therefore do not incorporate EdU into chromosomal DNA, which would obscure the detection of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 57 publications
2
60
1
Order By: Relevance
“…Regardless, we failed to detect preferential PN localization using either the Provirus ViewHIV assay, which predominantly detects integrated HIV-1 (Figure S1), or the SCIP assay, which exclusively scores for integration (Figure 2B). We also note that visual inspection of images of MDM-infected cells are consistent with the notion that HIV-1 disperses fairly randomly throughout cell nuclei (Stultz et al, 2017). …”
Section: Discussionsupporting
confidence: 84%
“…Regardless, we failed to detect preferential PN localization using either the Provirus ViewHIV assay, which predominantly detects integrated HIV-1 (Figure S1), or the SCIP assay, which exclusively scores for integration (Figure 2B). We also note that visual inspection of images of MDM-infected cells are consistent with the notion that HIV-1 disperses fairly randomly throughout cell nuclei (Stultz et al, 2017). …”
Section: Discussionsupporting
confidence: 84%
“…However, it is not clear that this is how uncoating proceeds in other cell types. For example, it was recently reported that reverse transcription, nuclear localization, and loss of capsid took place at a slower rate in primary macrophages, as monitored by specific labeling of the viral DNA (38). Other circumstances in vivo may also show different kinetics of uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 capsid uncoating dependence on microtubule stability also supports a cytoplasmic uncoating (25,26,(30)(31)(32)(33)(34). Recently, the importance and dependence on CA of most of the early steps of infection have been partially explained by the identification of a small amount of CA that associates with the PIC in the nucleus (35)(36)(37)(38). Because of the differences between these models, the kinetics, dynamics, and cellular location of uncoating of infectious HIV-1 particles have remained controversial topics (4, 25-29, 37, 39, 40).…”
mentioning
confidence: 86%
“…Given the size of the viral core, the capsid (CA) shell has to disassemble or “uncoat” to allow the genome to pass through nuclear pores (Campbell and Hope, 2015). Although some CA can be detected in the nucleus and functions in processes after nuclear entry (Chen et al, 2016; Hulme et al, 2015; Koh et al, 2013; Peng et al, 2014; Schaller et al, 2011; Stultz et al, 2017), whether reverse transcription and uncoating occur during transport along MTs in the cytoplasm or at nuclear pores remains a matter of debate (Arhel et al, 2007; Fassati and Goff, 2001; Le Sage et al, 2014; McDonald et al, 2002; Miller et al, 1997; Rasaiyaah et al, 2013; Zhou et al, 2011). However, recent live cell imaging supports the notion that uncoating begins in the cytoplasm (Francis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent live cell imaging supports the notion that uncoating begins in the cytoplasm (Francis et al, 2016). Notably, uncoating and reverse transcription are intricately coupled processes (Cosnefroy et al, 2016; Hulme et al, 2011; Rankovic et al, 2017; Stultz et al, 2017; Yang et al, 2013) that are further intertwined with the bi-directional movement of HIV-1 particles. Interfering with MT or dynein function suppresses HIV-1 trafficking and delays uncoating during early infection (Arhel et al, 2006; Delaney et al, 2017; Lukic et al, 2014; Malikov et al, 2015; McDonald et al, 2002; Pawlica and Berthoux, 2014; Sabo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%